2021
DOI: 10.3389/fendo.2021.712107
|View full text |Cite
|
Sign up to set email alerts
|

FGF-Receptors and PD-L1 in Anaplastic and Poorly Differentiated Thyroid Cancer: Evaluation of the Preclinical Rationale

Abstract: BackgroundTreatment options for poorly differentiated (PDTC) and anaplastic (ATC) thyroid carcinoma are unsatisfactory and prognosis is generally poor. Lenvatinib (LEN), a multi-tyrosine kinase inhibitor targeting fibroblast growth factor receptors (FGFR) 1-4 is approved for advanced radioiodine refractory thyroid carcinoma, but response to single agent is poor in ATC. Recent reports of combining LEN with PD-1 inhibitor pembrolizumab (PEM) are promising.Materials and MethodsPrimary ATC (n=93) and PDTC (n=47) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 39 publications
1
22
0
2
Order By: Relevance
“…Among these inhibitory immune checkpoint molecules, PD-L1 expression has been identified in 70% of ATC samples in the pre-clinical study by Schürch et al [ 49 ] and in the phase I study of spartalizumab [ 10 ]. PD-L1 expression based on the proportion of stained tumor cells according to Tumor Proportion Score (TPS) has been found at ≥5% in 73% of 93 samples in a recent multicenter study from Germany [ 51 ]. In the tumor microenvironment, PD-L1 can be upregulated in both tumor cells and immune-microenvironment cells, such as TAMs in ATC samples [ 52 , 53 ].…”
Section: Pathology and Biology: How Do We Understand The Aggressivene...mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these inhibitory immune checkpoint molecules, PD-L1 expression has been identified in 70% of ATC samples in the pre-clinical study by Schürch et al [ 49 ] and in the phase I study of spartalizumab [ 10 ]. PD-L1 expression based on the proportion of stained tumor cells according to Tumor Proportion Score (TPS) has been found at ≥5% in 73% of 93 samples in a recent multicenter study from Germany [ 51 ]. In the tumor microenvironment, PD-L1 can be upregulated in both tumor cells and immune-microenvironment cells, such as TAMs in ATC samples [ 52 , 53 ].…”
Section: Pathology and Biology: How Do We Understand The Aggressivene...mentioning
confidence: 99%
“…PD-L1 has been suggested as a predictive biomarker of response to ICI in several cancers although its robustness has been questioned. As described above, PD-L1 is often expressed on ATC tumor cells, suggesting new treatment opportunities for ATC with immunotherapy [ 10 , 51 ]. Indeed, spartalizumab, an anti-PD-1 antibody, has been studied in ATC [ 10 ].…”
Section: Treatment: To Treat Aggressively or To Palliate The Symptoms?mentioning
confidence: 99%
“…A prospective multicentric phase II trial did not confirm the encouraging results of a Japanese phase II study of lenvatinib in ATC patients and was interrupted due to the absence of efficacy [ 18 , 19 ]. Recent studies suggested that one start the treatment with lenvatinib alone and add pembrolizumab upon disease progression [ 4 , 20 , 21 , 22 ]. However, some TKIs induce modifications of the tumor environment that inhibit the anti-tumor immune response, thus contributing to immune resistance and progression of disease [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…RNAScope is a custom RNA in-situ hybridization solution from Advanced Cell Diagnostics, USA. Version 2.0 of the kit was utilized for our experiments following the manufacturer’s instructions as described before ( 40 ). In short, the FFPE tissue sections of ~2µm thickness were mounted on SuperFrost glass slides (Langenbrinck, Germany), deparaffinized in xylene then washed with 100% ethanol followed by endogenous enzyme blocking in hydrogen peroxide solution (ref.…”
Section: Methodsmentioning
confidence: 99%